Left Atrial Appendage Conduction Jump for Real‐Time Evaluation of Conduction Block Over the Anterior Mitral Annulus Line. (8th May 2015) - HUEMER, MARTIN; WUTZLER, ALEXANDER; PARWANI, ABDUL SHOKOR; ATTANASIO, PHILIPP; HEIDERFAZEL, SALMAN; EWERTSEN, NIELS CHRISTIAN; HAVERKAMP, WILHELM; BOLDT, LEIF‐HENDRIK
LAA Conduction Jump for Real‐Time Evaluation Introduction Evaluation of conduction over a linear ablation lesion at the anterior mitral annulus can be time‐consuming and difficult during ongoing radiofrequency application. The purpose of this study was to validate conduction time from the beginning of the p wave and from the coronary sinus ostium to the left atrial appendage (LAA) as a new method of conduction block surveillance. Methods Conduction across the anterior mitral annulus line was evaluated using a total of 55 patients. We verified completeness of conduction block by standard techniques including differential pacing, double potential mapping and activation mapping. Those methods were compared to the new method of observing an abrupt prolongation of conduction time into the LAA as well as a conduction sequence change on a circular multipolar mapping catheter placed inside the LAA during sinus rhythm. Results Bidirectional conduction block across the ablated line was achieved in 51 (92.7%) of the patients. Prior to ablation, mean conduction time across the line was 59 ± 21 milliseconds. This value increased to 163 ± 43 milliseconds after a successful ablation. An abrupt prolongation of conduction time into the LAA of at least 50 milliseconds was observed in all patients at the moment when a complete conduction block was achieved. Additionally, a change of conduction sequence recorded with the multi‐electrode catheter placed in the LAA was observed in all of these patients. Conclusions A sudden jump of p wave and coronary sinus ostium to LAA conduction time together with a change of conduction sequence recorded with a multi‐electrode catheter placed inside the LAA during sinus rhythm is a simple and reliable approach for beat‐to‐beat surveillance of conduction block across the anterior mitral annulus during radiofrequency ablation.